Implementation of Learning Methods Directly in An Effort to Improve the Ability to Writing Poetry of Grade XI Students’ High School 1 Padang - Siregar, Ahmad Firdaus; Sutikno, Sutikno (PT Inovasi Pratama Internasional, 2025)
The problems in this research are: 1) How is the process of implementing direct learning methods to improve poetry writing skills among Class XI students at State Senior High School 1 Padang Bolak Julu in the 2024-2025 academic year? 2) How is the improvement in students' poetry writing skills in the same class and academic year through the use of direct learning methods? This study aims to: 1) Identify the process of applying direct learning methods to enhance students' poetry writing skills; 2) Determine the improvement in students' poetry writing skills through the use of direct learning methods. The research method used is Classroom Action Research (CAR), involving 40 students of Class XI at State Senior High School 1 Padang Bolak Julu in the 2024-2025 academic year. The object of this study is the students' poetry writing results, and the data collection instrument is an essay test. The findings show that using the direct learning method improves students' poetry writing skills from cycle I to cycle III. The average score increased from 64 in cycle I to 72.5 in cycle II and 83.16 in cycle III. Learning completeness also improved, with 47.5% of students completing learning in cycle I, increasing to 72.5% in cycle II, and reaching 87.5% in cycle III, categorized as good. These results confirm the research hypothesis that the direct learning method effectively enhances students' poetry writing skills.